Filipinos representation for the self.[article]. - Sta.Maria, Madelene
Specific meaning-systems were identified that are associated with the Self or Selfhood. These make apparent the norms, beliefs, values, and dimensions of behavior which may be significant in a given group to enable one within the group to understand and communicate one's actions. Analyses on descriptions of informants about themeselves and others show that to be understood and to understand the other, and to obtain the identity within the group, the value of exhibiting one's responsibility to one's relationship with the other becomes important. The concept of loob is found to be that which integrates experiences and which functions in the individual's decisions about how he/she should behave. It ios within this frame or reference that one embeds pagmamalasakit, pagsusumikap, paghahayag ng kalooban, paglalago ng kalooban, pagkamasayahin, pagkamatapat-actions associated with Representations for the Self as it is understood and whose meaning is lived in interactiona with others.